2014
DOI: 10.3390/s141018982
|View full text |Cite
|
Sign up to set email alerts
|

Chemoresistive Gas Sensors for the Detection of Colorectal Cancer Biomarkers

Abstract: Numerous medical studies show that tumor growth is accompanied by protein changes that may lead to the peroxidation of the cell membrane with consequent emission of volatile organic compounds (VOCs) by breath or intestinal gases that should be seen as biomarkers for colorectal cancer (CRC). The analysis of VOCs represents a non-invasive and potentially inexpensive preliminary screening technique. An array of chemoresistive gas sensors based on screen-printed metal oxide semiconducting films has been selected t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 19 publications
3
38
0
Order By: Relevance
“…However, it can be noticed that the TiTaV sensor (titanium, tantalum, vanadium oxides) was not sensitive to it, and it showed a great selectivity to small quantities of C 6 H 6 even in the presence of hydrogen. This confirms the good capability of TiTaV to detect benzene only [1] or in presence of interferers (Figs. 9 and 10).…”
Section: Methodssupporting
confidence: 87%
See 3 more Smart Citations
“…However, it can be noticed that the TiTaV sensor (titanium, tantalum, vanadium oxides) was not sensitive to it, and it showed a great selectivity to small quantities of C 6 H 6 even in the presence of hydrogen. This confirms the good capability of TiTaV to detect benzene only [1] or in presence of interferers (Figs. 9 and 10).…”
Section: Methodssupporting
confidence: 87%
“…14, the ZnO 850 sensor (zinc oxide, fired at 850 • C) and STN (tin, tantalum, niobium oxides) are the ones that give the best responses to this compound, confirming results for tin oxidebased sensors of a previous work [1], in wet conditions. Humidity does not change the trend of the responses to 1-iodo-nonane but reduces only their value.…”
Section: -Iodo-nonane (C 9 H 19 I)supporting
confidence: 87%
See 2 more Smart Citations
“…Therefore, the importance of an additional screening system lies in the decrease of false positive rate, to reduce the number of non-operative colonoscopies, risky for elderly and debilitated patients. Previous works by our team have shown that chemoresistive sensors are capable of detecting tumor biomarkers in very low concentrations (tenths of ppb) [3,4]. The technique presented here employs a patented device [5] named SCENT A1, made of a core of five chemoresistive sensors.…”
Section: Introductionmentioning
confidence: 99%